PENINGKATAN KEMAMPUAN PENGUKURAN DALAM MATEMATIKA AWAL MELALUI METODE DISCOVERY LEARNING - Tesya cahyani Kusuma (Tumbuh Kembang: Kajian Teori dan Pembelajaran PAUD, 2017)
This study aims to determine the increase measurement in early math skills in early childhood learning through discovery methods. The research was conducted on a group B2 Kindergarten Pertiwi I Kantor Gubernur Padang with of fifteen children. The research was conducted from March to April 2015. This study used action research by Kemmis and Taggart. This study consisted of two cycles, each cycle consisting of 8 sessions. Each cycle has four main activities: planning, action, observation and reflection. Analysis of the data used quantitative and qualitative approaches. Analysis of quantitative data used descriptive statistics that compare the results obtained from the Pre cycle, first cycle and the second cycle. While the analysis of qualitative data used analyzing data from the field notes and interviews during the research by steps of data reduction, data display and data verification . The results showed an increase measurement in Early Mathematics Ability in early childhood B2 group conducted through discovery learning method. In the pre-cycle measurement in Early Mathematics level of Ability percentage yield 45.90%, in measurement in Early Mathematics level of Ability increased to 65.83% after the act of the first cycle and level increased to 89.10% second cycle becomes. Discovery Learning Methods stimulate student observer, classification, measure, guess and infer for increase measurement in Early Mathematics Ability